Association of MicroRNA-146a and MicroRNA-149 Polymorphisms With Strokes in Asian Populations: An Updated Meta-Analysis. (November 2017) - Du, Jiaxiu; Cui, Chuanju; Zhang, Shuling; Yang, Xiaopeng; Lou, Jiyu
Strokes are a major cause of disability and death worldwide. An association between microRNA-146a (miR-146a) and miR-149 polymorphisms and strokes was inconclusive. This meta-analysis aimed to reevaluate the strength of the association by searching online databases and retrieving relevant case–control studies published between 2000 and 2016. Nine articles including 8 on miR-146a rs2910164 G/C and 3 on miR-149 rs2292832 C/T in 3372 patients with stroke and 4394 controls were included. The miR-149 rs2292832 was significantly associated with the risk of a stroke under allelic (C vs T: odds ratio [OR] = 1.14; 95% confidence interval [CI] = 1.01-1.29; P = .03), homologous (CC vs TT: OR = 1.36; 95% CI = 1.05-1.77; P = .02), and recessive models (CC vs CT + TT: OR = 1.34; 95% CI = 1.05-1.71; P = .02). No correlation was detected between miR-146a rs2910164 and susceptibility to a stroke. In conclusion, the results suggested that miR-149 might be a risk factor for the development of a stroke, while miR-146a might not be. Well-designed studies with large populations are needed to clarify the association between miR-146a and miR-149 polymorphisms and strokes.